Peran Pemediasi Efikasi Diri Kreatif Pada Hubungan Antara Persepsi Terhadap Kepemimpinan Transformasional Pada Kreativitas Karyawan - Elfitra Azliyanti; Purbo Jadmiko; Wiry Utami (UIN Raden Mas Said Surakarta, 2019)
This study aims to identify and analyze the role of perception of transformational leadership and creative self-efficacy of employee (lecturer) creativity. The research methodology used is explanatory research through hypothesis testing. The object and population of this study are Bung Hatta University Lecturers. The sampling technique used was purposive sampling with sample criteria was Bung Hatta University Lecturer who had working period more than 1 (one) year (n = 170). The data analysis technique in this study use SEM-PLS (Smart PLS). This study consists of four hypotheses and the research results obtained from the study of perceptions of transformational leadership has no effect on employee creativity, perceptions of transformational leadership have a positive effect on creative self- efficacy. Creative self-efficacy has a positive effect on employee creativity and creative self-efficacy mediates the relationship of perception of transformational leadership on employee creativity